2008
DOI: 10.1136/jmg.2008.061259
|View full text |Cite
|
Sign up to set email alerts
|

In vitro splicing analysis showed that availability of a cryptic splice site is not a determinant for alternative splicing patterns caused by +1G->A mutations in introns of the dystrophin gene

Abstract: It was concluded that sequences inserted into the in vitro splicing assay minigene contain cis-elements that determine splicing pathways. By taking other +1G-->A mutations in the introns of the dystrophin gene reported in the literature into consideration, it seems that cryptic splice-site activation is seen only in strong exons. This finding will help to elucidate the molecular pathogenesis of dystrophinopathy and to predict efficiency of induction of exon skipping with antisense oligonucleotides for treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…Confirming a previous work [56], our data indicate that the availability of cryptic splice site does not determine the main splicing pathway, since numerous potential sites are found in most analyzed exons according to HSF and MaxEnt predictions. Habara et al proposed that in +1G>A mutations a strong exon recognition, resulting from the combination of a high 3′ ss score and a long exon length, is necessary for cryptic site activation [56]. Our data indicate that the splicing pathway in 5′ ss mutations is determined by the interplay between the relative strength of 3′ ss and the density of ESE elements (Figure 3).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Confirming a previous work [56], our data indicate that the availability of cryptic splice site does not determine the main splicing pathway, since numerous potential sites are found in most analyzed exons according to HSF and MaxEnt predictions. Habara et al proposed that in +1G>A mutations a strong exon recognition, resulting from the combination of a high 3′ ss score and a long exon length, is necessary for cryptic site activation [56]. Our data indicate that the splicing pathway in 5′ ss mutations is determined by the interplay between the relative strength of 3′ ss and the density of ESE elements (Figure 3).…”
Section: Discussionsupporting
confidence: 85%
“…The abundance of cryptic splice sites has been suggested as a main factor determining whether a mutation induces exon-skipping or cryptic splice site activation [55]. Confirming a previous work [56], our data indicate that the availability of cryptic splice site does not determine the main splicing pathway, since numerous potential sites are found in most analyzed exons according to HSF and MaxEnt predictions. Habara et al proposed that in +1G>A mutations a strong exon recognition, resulting from the combination of a high 3′ ss score and a long exon length, is necessary for cryptic site activation [56].…”
Section: Discussionsupporting
confidence: 81%
“…The splicing pathway affected by these mutations differed from mutation to mutation. 33 Exon skipping was occurring in 12 cases. Cryptic splice site activation occurred in 12 cases, and in 3 cases both exon skipping and cryptic splice site activation occurred.…”
Section: Splice Site Mutationsmentioning
confidence: 99%
“…The splicing effect caused by theses mutations includes exon skipping and activation of a cryptic splice site [Hertel, 2008;Anna et al, 2018]. The definite splicing effects may relate to the strength of canonical and cryptic splice sites, exon and intron length, the order of intron removal, the abundance of exonic splice enhancers and silencers, or a RNA secondary structure [Takahara et al, 2002;Tazon-Vega et al, 2007;Habara et al, 2009;Anna et al, 2018]. In our study, the results of the minigene assay showed that both c.2917+1G>A and c.2917+1G>C mutations had 3 functional consequences: 2 of them caused the skipping of 1 or 2 exons, and the third transcript activated a donor cryptic splice site located at position c.2820-2821.…”
Section: Discussionmentioning
confidence: 99%